Cimicifuga racemosa as floral Selective Estrogen Receptor Modulator - Bodera, Paweł; Poznański, Sebastian (Menopause Review/Przegląd Menopauzalny, 2005)
Selective Estrogen Receptor Modulators (SERMs) are characterized by their ability to act as either estrogen agonists or antagonists in different tissues, with different genes, and in different hormonal milieux. The effects of the SERMs are partially understood by their interactions with the ligand binding pocket of the estrogen receptors (ER) a and b. Extracts of Black cohosh ( Cimicifuga racemosa ) have been used for the treatment of climacteric complaints since decades. Efficacy, particularly concerning neurovegetative and psychic symptoms, has been proven in clinical trials. A unknown substances with Selective Estrogen Receptor Modulator (SERM) activity as active principle have been assumed. Recently, evidence arose that Cimicifuga racemosa may also contain dopaminergic compounds, which may contribute to the therapeutic activity of the extract.